Bibliometric review on psychological well-being in the Journal of Research Psychology - UNMSM (1998-2022) - Díaz Fernández, Tania (2023)
A bibliometric analysis was carried out in the Revista de Psicología of the Universidad Nacional Mayor de San Marcos regarding Psychological Well-being, from 1998 to 2022. The exact number of published articles, the method used, the population studied, and the number of articles published were analyzed. the contents of the works. With 25 volumes, 12 research papers and 38 authors as first signatories, giving an average of 0.3 authors per paper. The results showed a greater focus on the university population with a notorious predilection in terms of the use of instruments for the Carol Ryff Psychological Well-Being Scale. Articles worked on by multiple authors predominate over individual articles; and a large part of these include variables related to academic performance, persistence, and self-esteem, which is consistent with various articles carried out in educational settings. Relevant findings and reflections on the outcomes identified from the review emerged.